Decision‐making under uncertainty for species introductions into ecological networks - Van Kleunen, Lucy B.; Peterson, Katie A.; Hayden, Meghan T.; Keyes, Aislyn; Schwartz, Aaron J.; Li, Henry; Dee, Laura E. (Ecology letters, 2023)
Ecological communities are increasingly subject to natural and human‐induced additions of species, as species shift their ranges under climate change, are introduced for conservation and are unintentionally moved by humans. As such, decisions about how to manage ecosystems subject to species introductions and considering multiple management objectives need to be made. However, the impacts of gaining new species on ecological communities are difficult to predict due to uncertainty in introduced species characteristics, the novel interactions that will be produced by that species, and the recipient ecosystem structure. Drawing on ecological and conservation decision theory, we synthesise literature into a conceptual framework for species introduction decision‐making based on ecological networks in high‐uncertainty contexts. We demonstrate the application of this framework to a theoretical decision surrounding assisted migration considering both biodiversity and ecosystem service objectives. We show that this framework can be used to evaluate trade‐offs between outcomes, predict worst‐case scenarios, suggest when one should collect additional data, and allow for improving knowledge of the system over time. We synthesise literature from several subdisciplines (e.g. invasion ecology, food web theory and conservation decision science) into a framework for decision‐making related to species introductions under uncertainty and multiple management objectives. Throughout, we highlight sources of uncertainty and suggest how this uncertainty can be carried through the prediction process. With our application, we show that this framework can be used to reveal important trade‐offs among objectives and worst‐case scenarios, suggest cases in which more data should be collected before making a decision, and allow for testing of ecological theory and improving knowledge of the system over time.